Enforcement of Criminal Sanctions for Corruptors with Certainty and Legal Justice - sitihumulhaer; Annie Myranika (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Corruption is an extraordinary crime because of its broad impact on the social, political, and economic life of a country. In the context of a state of law, the enforcement of criminal sanctions against perpetrators of corruption must be based on the principles of legal certainty and justice. However, in practice, various problems are still found, such as disparity in sentencing, inconsistent sentencing, and weak deterrent effects. This study aims to examine how the implementation of criminal sanctions enforcement against corruptors can reflect legal certainty and justice in Indonesia. The method used is a normative legal approach with an analysis of laws and regulations, court decisions, and relevant case studies. The results of the study show that even though an adequate legal framework is available, the enforcement of criminal sanctions still faces obstacles in terms of the independence of law enforcement agencies, varying interpretations of the law, and the influence of certain interests in the judicial process. Therefore, a more consistent and transparent reform of the criminal justice system is needed, as well as strengthening coordination between law enforcement officers in order to realize law enforcement that is not only certain, but also fair for all parties. Keywords: Corruption, Criminal Sanctions, Legal Certainty, Legal Justice, Law Enforcement.